An Analysis of Electricity Generation, Supply, and Economic Growth in Selected SADC Countries - Hlongwane, Nyiko Worship; Lenoke, Mpho; Daw, Olebogeng David (International Journal of Energy Economics and Policy, 2023)
The study analysed electricity generation, supply, and economic growth in selected SADC countries. The study utilised panel data spanning from 1990 to 2020 collected from secondary sources such as the World Bank and International Energy Agency. The study conducted unit root tests, cointegration tests, optimal lags length criterion, panel ARDL, Dumitrescu-Hurlin causality and residual diagnostics tests. The results revealed that in the short run, electricity generation and supply are insignificant determinants of economic growth. However, in the long run, electricity generation and supply are significant determinants of economic growth in selected SADC countries. The study recommends restructuring and maintaining electricity generation facilities to boost economic growth in the region.